The Vocalic Quality and Vocalic Quantity in the Speech of TV News Presenters on ČT 1 - Kopečková, Michaela (Bohemica Olomucensia, 2016)
The article is based on the methodology and ongoing phonetic research of the vocalic quality and quantity which will be part of my Ph.D. dissertation. The analysis focuses on the vocalic quality as well as on the quantity ratio in long and short vowels produced by TV news presenters. The research aims to find out whether the vocalic quality and quantity are influenced by the phonemic neighbourhood and by the position of the analyzed vowel within sample word.
Keywords: phonetics; vowels; vocalic quality; vocalic quantity; analysis; TV news; orthoepy